2014
DOI: 10.1080/10255842.2014.916700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cup inclination on predicted contact stress-induced volumetric wear in total hip replacement

Abstract: In order to increase the lifetime of the total hip endoprosthesis, it is necessary to understand mechanisms leading to its failure. In this work, we address volumetric wear of the artificial cup, in particular the effect of its inclination with respect to the vertical. Volumetric wear was calculated by using mathematical models for resultant hip force, contact stress and penetration of the prosthesis head into the cup. Relevance of the dependence of volumetric wear on inclination of the cup (its abduction angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, it has been shown that this could be unfavorable in terms of dislocation [27]. The aim of this work was to provide an answer to the question posed by the results of previous work [27]: whether arthroplasties that have suffered dislocation have a less favorable stress distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it has been shown that this could be unfavorable in terms of dislocation [27]. The aim of this work was to provide an answer to the question posed by the results of previous work [27]: whether arthroplasties that have suffered dislocation have a less favorable stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, the hip stress distribution can be calculated in a neutral hip position during a one-legged stance, using a standard X-ray image of the hip and pelvis. It has been validated by clinical studies considering various pathologies in native hips [23,24] and in hips with total hip arthroplasties [2527].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this takes place at the acetabular rim, the peak stress is calculated according to the expression p max ¼ p 0 cos ðϑ CE À ΘÞ [5]. It was shown that biomechanical parameters calculated with HIPSTRESS models for resultant hip force and contact hip stress were useful in explaining early osteoarthritis in dysplastic hips [7], hips with primary osteoarthritis, hips subject to avascular necrosis of the femoral head [5], hips that were in childhood subject to the Perthes disease [8], effect of different osteotomies [9][10][11][12], and the direction and volumetric wear of total hip endoprosthesis [13]. Evidently, the models include the relevant parameters of the individual hip to have a predictive value.…”
Section: Hipstress Model For Contact Stress In the Hipmentioning
confidence: 99%